(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Brinjal is an important economic flowering vegetable crop that belongs to the family solanaceae. Fruitful brinjal production in our nation is restricted by several biotic and abiotic factors including weeds. Weeds compete with the main crop for growth resources like nutrients, moisture, sunlight and space affecting the yield of the crop. In addition, it also acts as alternate hosts that harbour insect-pests and diseases ultimately resulting in huge crop loss. Thus, with the objective of finding suitable measures to control weeds for obtaining higher quality yield in brinjal, a field experiment was undertaken at Horticultural Research Centre, Chauras Campus, Department of Horticulture, H.N.B. Garhwal University, Srinagar, Garhwal, Uttarakhand to evaluate the effect of different concentrations of pre-emergence herbicides in brinjal Cv. Pant Rituraj under subtropical condition of Garhwal Hills. The experiment was laid-out in randomized block design with three replications. The treatments of the experiment were comprised of different pre-emergence herbicides with applied at doses along with the hand weeding operation. The result of the experiment revealed that among all the treatments used, treatment T1 comprising of Alachlor 50% EC @ 1.0 kg a.i ha-1 + hand weeding at 45 DAT resulted in better performance in terms of weed index, number of marketable fruits, average fruit weight, yield per plot and cost benefit ratio followed by treatment T2 Alachlor 50% EC @ 1.5 kg a.i ha-1 + hand weeding at 45 DAT. Therefore, pre-emergence herbicide such as Alachlor 50% EC @ 1.0 kg a.i ha-1 + hand weeding at 45 DAT can be used to control weeds and to obtain higher quality yield in brinjal under subtropical condition of Garhwal hills.